Kebijakan Pemerintah India dalam Menghadapi Fenomena Dowry Death yang Terjadi di Dalam Masyarakat di India - Hendrawan, Iqbal; Zid, Muhammad; Jalaludin, Muzani (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The phenomenon of dowry death in India refers to the tragic and often violent death of married women due to unmet dowry demands, which are deeply rooted in the country’s caste-based social structure and patriarchal norms. Despite the existence of legal instruments and awareness campaigns, such incidents remain prevalent, particularly in communities with strong traditional values. This study aims to analyze the Indian government's policies in addressing dowry-related violence and examine the effectiveness of these measures. Using a qualitative non-interactive approach with content analysis, the research draws on scholarly journals, government documents, and reports that discuss the dowry system and related deaths. The findings reveal that although several legal regulations such as the Dowry Prohibition Act, IPC Section 498A, and Domestic Violence Act have been enacted, dowry deaths persist due to gaps in law enforcement, social acceptance of dowry, and the continued influence of caste and gender hierarchies. The study concludes that dowry-related violence cannot be effectively eliminated through legal means alone; a deeper transformation in societal attitudes, gender roles, and traditional expectations is essential to reducing dowry deaths in India.